ANALISIS KELAYAKAN USAHATANI TEMBAKAU RAKYAT DI KECAMATAN MOYO HILIR KABUPATEN SUMBAWA - Ririn Wahyu Agustin; Siti Nurwahidah; Lukman Hakim; Yadi Hartono; Nila Wijayanti (JURNAL SOSIAL EKONOMI PERTANIAN, 2026)
Tobacco farming plays an important role in increasing farmers' income; however, an assessment of its economic feasibility is necessary to ensure the sustainability of its management. This study aimed to analyze the revenue and financial feasibility of tobacco farming in Moyo Hilir District, Sumbawa Regency. The research was conducted in June 2025 using a purposive sampling method involving 60 respondents, with the sample size determined using the Slovin formula. Primary data were collected through direct interviews with farmers. The analysis included the calculation of fixed costs, variable costs, total production costs, total revenue, and the Revenue-Cost (R/C) ratio. The results showed that the average annual fixed cost was IDR 1,462,505, the average annual variable cost was IDR 1,105,650, and the average annual total cost was IDR 2,568,155. Meanwhile, the average annual revenue reached IDR 26,958,333. The R/C ratio was 14.37, indicating that tobacco farming in Moyo Hilir District is economically feasible and highly profitable. These findings suggest that tobacco farming has strong potential to improve farmers' welfare. However, its long-term sustainability should be supported by improved production efficiency and appropriate agricultural policies.